(untitled) (Revista Electrónica REDINE, 2018)
In the conception constructivista, the subject and the object join the process of construction of the knowledge, which, it stops being a linear representation of what happens in the reality, independently of the man who constructs it. The knowledge not only is determined by schemes and innate and / or acquired capacities, but the needs of self-organization and development of the own subjective system, in this respect, it enters game the sociocultural context where one is immersed.